DNA nanotechnology from the test tube to the cell - Chen, Yuan-Jyue; Groves, Benjamin; Muscat, Richard A.; Seelig, Georg (Nature Nanotechnology, 2015)
The programmability of Watson–Crick base pairing, combined with a decrease in the cost of synthesis, has made DNA a widely used material for the assembly of molecular structures and dynamic molecular devices. Working in cell-free settings, researchers in DNA nanotechnology have been able to scale up system complexity and quantitatively characterize reaction mechanisms to an extent that is infeasible for engineered gene circuits or other cell-based technologies. However, the most intriguing applications of DNA nanotechnology — applications that best take advantage of the small size, biocompatibility and programmability of DNA-based systems — lie at the interface with biology. Here, we review recent progress in the transition of DNA nanotechnology from the test tube to the cell. We highlight key successes in the development of DNA-based imaging probes, prototypes of smart therapeutics and drug delivery systems, and explore the future challenges and opportunities for cellular DNA nanotechnology.